Molecular Characteristics and Identification of Lactic Acid Bacteria of Pineapple Waste as Probiotics Candidates for Ruminants - Syarif, Mardalena, S.; Erina, S. (Pakistan Journal of Nutrition, 2016)
The current study aims to identify the potential of lactic acid bacteria (LAB) from pineapple waste as candidate probiotics for ruminants. LAB were isolated from the skin of ripe pineapple (Ananas comosus L. Merr). Pineapple skin was crushed in a chopper then placed in a sealed container and stored in an aerobic conditions for a week. LAB antimicrobial tests were conducted on four types of pathogenic bacteria E. coli (NBRC14 and 237), Staphylococcus aureus (NBRC13 and 267), Bacillus cereus and Staphylococcus aureus). Bile tolerance testing was performed using 0.3% (w/v) and 0.5 (w/v) oxgall bile solution LAB grown only in MRS medium were used as a control. Tolerance to bile salts was calculated based on the log difference in the number of bacterial colonies growing under control versus treatment condition. The smaller the difference, the more tolerant LAB were to bile salts. Sequence analysis was performed using DNAstar software. Sequence alignment was analyzed by comparing the queried PCR sequences with those the NCBI Gene Bank data base using BLAST and then kinship examined with Clustal W. Lactobacillus plantarum isolates extracted from pineapple skin were able to live and thrive at room temperature for 6-h in storage and with stand a 0.3% (w/v) bile salts solution while maintaining optimum growth. These LAB were also able to inhibit the growth of pathogenic bacteria as Salmonella typhimurium, Escherichia coli, Bacillus cereus and Staphylococcus. The result suggest that LAB extracted from pineapple skin waste including L. plantarum and L. pentosus have the potential to be used as probiotics for ruminants.